Working for health in the Caribbean : PAHO/WHO Subregional Cooperation Strategy - 2016-2019 (PAHO/WHO Christ ChurchBB, 2016)
Reflects the work that PAHO/WHO will undertake over the period 2016-2019 in the Caribbean subregion, in collaboration with Member States of the Caribbean Community (CARICOM, the CARICOM Secretariat and other key partners. Complements the organisation's country level work and aligns with the vision of the PAHO Strategic Plan 2014-2019, adopted by Member States at the 52nd Directing Council in September 2013.
Keywords: HEALTH